Polyol Mediated Synthesis and Microstructural Features of Polycrystalline LiMPO4 (M = Mn and Co) Olivine Phosphates for Lithium Batteries - Padmanathan, N.; Selladurai, S. (Asian Journal of Chemistry, 2013)
Well crystalline LiMPO4 (M = Mn and Co) powder was synthesized via polyol mediated wet chemical route at low temperature. Glutinous diethylene glycol plays an important role during synthesis which provide reducing atmosphere, lessen the surplus agglomeration and hinders the particle growth. The phase and micro-structural features of the obtained olivine phosphate was analyzed by powder X-ray diffraction, scanning electron microscope and transmission electron microscope. X-ray diffraction analysis demonstrates that the sample exhibits pure orthorhombic structure with Pnma space group. Morphological scrutiny flaunts the formation of uniformly distributed nanosize particles appeared spherical in shape. The statistical mean diameter of the particles was approximately at 200 nm for LiMPO4 nanostructures. As prepared olivine micro/nanostructure can be more favorable for fast lithium insertion/extraction reaction. Using the proposed polyol technique, it is possible to obtain the well crystalline submicron and nano size olivine phosphates for high potential lithium battery applications.